PENERAPAN METODE EARNED VALUE ANALISIS (EVA) PADA PROYEK REPARASI KAPAL - Silas Tandi; Arie Indartono; Arum Nurvitasari; Dodiek Kurniawan (Proceedings Conference on Marine Engineering and its Application, 2023)
Delays in completing the project are things that must be avoided, because in addition to adversely affectingthe credibility of the contractor, it also causes losses in terms of project time and cost or cost overrun, where the workdone is not in accordance with the planned time and the cost is not in accordance with the budgeted so that it requiresadditional costs to complete the project. The Earned Value method is a method used to manage project costs andschedules in a structured manner. This method can provide information on the status of project performance in a reviewperiod and information on predicted costs and time for completion of all work based on performance indicators at thetime of review. Project performance on ship repair TB. Big Fair 15 from the calculation of CV and SV in reviews 1, 2and 3 is negative and so is the calculation of CPI and SPI in reviews 1, 2 and 3 is negative or less than 1. This indicatesthat the cost used to complete the project is greater than the plan. However, for the 4th review, the results of the CVand SV calculations show a positive value, which means that the cost of completing the project is in accordance withthe plan as well as the CPI and SPI at the 4th review show a positive value, which means that the cost of completingthe project is in accordance with the plan. Based on the analysis that has been done, the time required to complete theremaining work is 10 days and in this ship repair project there is a cost overrun of Rp. 107,332,706 with a cost budgetof Rp. 459,273,994. After a review using Earned Value Analysis, the results are obtained for each review, where review1 weighs 12.93% at a cost of Rp. 73,267,561 and review 2 weighs 45.17% at a cost of Rp. 255,915,724 and review 3weighs 26.58% at a cost of Rp. 86,839,784.